ERGONOMIC DESIGN OF THE CUTTING MACHINE FOR CHOPPING CYPERACEAE PLANT - Hartomo Soewardi; Lintang Zahrima Kalsum (Malaysian Journal of Public Health Medicine, 2020)
The manual cutting is still applied in the Small and Medium Industries (SMI) especially in cutting the Cyperaceae plant. One of the varieties is “Fimbristylis Globulosa (Mendong)”. This plant is used as a raw material to manufacture the handicraft. The process is commenced with chopping the plant by using a manual tool. However, the existing tool still causes some complains where 90% of users experienced discomfort and unsafe in the use. The tool is also not effective and efficient for cutting. Thus, it is significant to improve the better cutting tools. This objective of this study is to design the innovative and ergonomic cutting tools for satisfying user requirements. The survey was done to identify some discomfort. The participatory ergonomic method is applied to determine the specification of design on basis anthropometry data of users. Non-parametric statistical analysis is conducted to test the hypothesis. The results of this study show that the developed design is a valid to reduce the risk of work-related musculoskeletal disorders and more comfort and safer at 5% of the significant levels where the proposed design specification used electric motor system and pneumatic system.